Type III Secretion Protein, PcrV, Impairs Pseudomonas aeruginosa Biofilm Formation by Increasing M1 Macrophage-Mediated Anti-bacterial Activities - Yu, Hua; Xiong, Junzhi; Qiu, Jing; He, Xiaomei; Sheng, Halei; Dai, Qian; Li, Defeng; Xin, Rong; Jiang, Lu; Li, Qiaoqiao; Chen, Qian; Peng, Jin; et al. (Frontiers in Microbiology, 2020)
Pseudomonas aeruginosa biofilms employ a variety of strategies to hijack the host immune defense system to achieve chronic infection. However, the bacterial components that are involved in this process are not yet fully understood. PcrV, a needle tip protein of the P. aeruginosa type III secretion system, was downregulated during P. aeruginosa biofilm infection. The impaired expression of the P. aeruginosa pcrV gene is associated with attenuated immune activation and an increased percentage of M2 macrophages following P. aeruginosa biofilm infection. Treatment with exogenous PcrV produced from Escherichia coli elevated tissue inflammation and the percentage of M1 macrophages, resulting in reduction in the biofilm burden. Further analyses demonstrated the potential of PcrV to induce classically activated M1 macrophages as evidenced by the increased production of proinflammtory cytokines, and anti-bacterial mediators, including inducible nitric oxide synthase (iNOS) and reactive oxygen species (ROS), as well as increased phagocytosis of bacteria. Mechanistically, PcrV-mediated promotion of macrophage M1 polarization and phagocytosis occur through the activation of MAPKs and NF-κB signaling pathways. Collectively, these findings reveal a potential role of PcrV in skewing host immune defense to promote P. aeruginosa biofilm infection, and provide new insights into the therapeutic strategies for P. aeruginosa biofilm infection.